The antileishmanial activity of the antarctic brown alga Ascoseira mirabilis Skottsberg - Clementino, Leandro da Costa [UNESP]; Oda, Fernando Bombarda [UNESP]; Teixeira, Thaiz Rodrigues; Tavares, Renata Spagolla Napoleão; Colepicolo, Pio; Santos, André Gonzaga dos [UNESP]; Debonsi, Hosana Maria; Graminha, Márcia A. S. [UNESP] (Taylor & Francis, 2020)
Leishmaniasis is a group of diseases that have limited and high toxic therapeutic options. Herein, we evaluated the antileishmanial potential and cytotoxicity of hexanic extract obtained from the Antarctic brown alga Ascoseira mirabilis using bioguided fractionation against Leishmania amazonensis and murine macrophages, which was fractionated by SPE, yielding seven fractions (F1-F7). The fraction F6 showed good anti-amastigote activity (IC50 = 73.4 ± 0.4 μg mL−1) and low cytotoxicity (CC50 > 100 μg mL−1). Thus, in order to identify the bioactive constituent(s) of F6, the fraction was separated in a semipreparative HPLC, yielding four fractions (F6.1-F6.4). F6.2 was the most bioactive fraction (IC50 = 66.5 ± 4.5 μg mL−1) and GC-MS analyses revealed that the compounds octadecane, propanoic acid, 1-monomyristin and azelaic acid correspond to 61% of its composition. These data show for the first time the antileishmanial potential of the Antarctic alga A. mirabilis.
Keywords: Antarctic macroalgae; Ascoseiraceae; Brown algae; Cutaneous leishmaniasis; GC-MS; Natural products